Introduction: Integrated history and philosophy of science in practice. (April 2015) - Arabatzis, Theodore; Howard, Don
Highlights: A special issue with nine papers from the &HPS4 Conference. The conference was held at the University of Athens, March 15–18, 2012. The papers integrate history of science and philosophy of science in various ways.